Bud and shoot structure may relate to the distribution area of South American Proteaceae tree species - Magnin, Noel Amaru (2012)
The capacity of preformation and neoformation and the structure of winter buds are vegetative attributes that may vary between plant species and according to ontogenetic stages of the same species. The present study describes and evaluates these features for the four tree species of Proteaceae occurring in Patagonia. In particular, it analyzes the structure and development of the distal buds of the trunk and the preformed or neoformed nature of the organs involved. Two of the species, Embothrium coccineum and Lomatia hirsuta, have scaly buds, in which primordia of green leaves are covered by cataphylls. The shoots of both species may include neoformed organs, more frequently so in juvenile trees. Lomatia ferruginea and Gevuina avellana have naked buds with a low number of primordia; in juvenile and adult trees of both species trunk shoots are entirely preformed. The structure of buds and shoots suggests two different growth modalities of the axes, which would be related to ecological breadth (narrower in the species with naked buds than in those with scaly buds) and distribution area of these species. The considerable morphological differences between the two Lomatia species studied raise the question whether they ought to be included in the same genus.